Convergent access to mono-fluoroalkene-based peptidomimetics. Issue 6 (25th January 2022) - Larnaud, Florent; Calata, Charlène; Prunier, Anaïs; Le Guen, Clothilde; Legay, Rémi; Pfund, Emmanuel; Lequeux, Thierry
Abstract : Expeditive racemic synthesis of monofluoroalkene peptide isosteres from aldehydes and substituted aromatic sulfones is reported. The olefination reaction is highly Z -selective from substituted aldehydes to afford transoid peptide mimic precursors. Abstract : The convergent and selective preparation of ( Z )-monofluoroalkene-based dipeptide isosteres from functionalized fluorosulfones as a cornerstone is described. In this approach, the N -terminal amino group is introduced by a conjugate addition reaction of phthalimide onto fluorinated vinylsulfones containing α-amino-acid side chains while the C -terminal motif is linked to the fluorovinylic peptide bond mimic via the Julia–Kocienski reaction between fluorosulfones and substituted aldehydes bearing α-amino-acid side chains.